Impacts of the Fed Corporate Credit Facilities through the Lenses of ETFs and CDX - Stefania D'Amico; Vamsidhar Kurakula; Stephen M. Lee (Federal Reserve Bank of Chicago, 2020)
In this study, we use the liquid and efficient bond ETF prices and CDX spreads to quantify the effects of the announcements of the Primary and Secondary Market Corporate Credit Facilities on the underlying corporate bonds. We find that those announcements triggered: (i) large and positive jumps in the prices of directly-eligible ETFs as well as ETFs holding eligible bonds and their close substitutes; (ii) a discrete drop in the perceived credit risk of eligible bonds especially following the April 9th announcement; (iii) a roaring back of investment-grade issuance and a pick-up in high-yield issuance. Importantly, across all ETFs in our sample, the magnitude of their price response does not seem directly related to the size of the reduction in either credit risk or liquidity risk, but rather appears to reflect mostly the eligibility of the ETF and its underlying bonds at the Federal Reserve facilities. This leads us to believe that the main factor driving the reaction to the announcements might be the elimination of "disaster risk" for eligible issuers.
Keywords: E43; E44; E52; E58; 330; Balance Sheet Policy; Credit Easing; Corporate bond market